KEPUTUSAN KONSUMEN DALAM PEMBELIAN WINE COFFEE DI NA COFFEE BANDA ACEH - Zulkarnain Zulkarnain; Noval Fazari; Widyawati Widyawati; Bagio Bagio; Yenny Ertika (Universitas Teuku Umar, 2020)
Wine coffee is a new type of beverage in Banda Aceh. This drink is sold in the price range of Rp 50,000 to Rp 75,000 per serving. Compared to other coffee beverage products, the price of wine coffee is the most expensive. Therefore, consumers' decision to buy wine coffee is greatly influenced by promotion,accessibility, and taste. This study aims to analyze the factors that influence consumer behavior to buy wine coffee and take the location of research at NA Coffee Premium, a coffee shop located in Lampineung, downtown Banda Aceh. Consumer behavior is measured using a Likert scale. The results showed that the score of consumer behavior is 4. Which means that the assessment shows a positive value because it exceeds the middle value. While the factors that influence consumer behavior in buying wine coffee at NA Coffee Premium are promotion, trust, accessibility, taste and texture. Significant value from Chi Square analysis on gender, age, education and occupation variables shows that promotion, trust, accessibility, taste and texture have values lower than 0.05.Keywords: Consumer Behavior, Purchase Decision Factor, Wine coffee